Preventing Foodborne Illness: Campylobacteriosis - Soohyoun Ahn; Renée M. Goodrich-Schneider; Keith R. Schneider (EDIS)
Over 800,000 cases per year of diarrheal disease in the United States were linked to Campylobacter, being ranked No. 4 in the pathogens causing foodborne illnesses. Campylobacter is also responsible for 15% of foodborne illness-related hospitalizations, and 6% of foodborne illness-related deaths. This revised 5-page fact sheet was written by Soohyoun Ahn, Renée M. Goodrich-Schneider, and Keith R. Schneider, and published by the UF Department of Food Science and Human Nutrition, July 2012.